A Study on Barriers and Practices of Supply Chain Social Sustainability in Indian and North American Energy and Manufacturing Sectors - Prashant Unnikrishnan Nair; Parvathy Thankamony (International Journal of Engineering and Management Research, 2021)
The paper paves a way to understand supply chain social sustainability practices and their associated barriers to implementation in the Indian and North American energy and manufacturing sectors. A systematic literature review and 4-point Likert scale survey provide clarity on the barriers and their perception from an industrial perspective. Findings from this study highlight that while the criticality of barriers differs with industry and geographies, some barriers are common to all. The study also highlights an approach needed for these sectors by identifying the most common barriers by providing a clear path on what practices can bring about the most impact in resolution. 20 barriers are identified, of which 3 show a stark difference in perception on its criticality against current published research work. The paper also identifies the top barriers along with the practices that make it most easy to implement. 11 common barriers that exist in the target industries of the two countries are identified and 6 easiest-to-resolve barriers are revealed, analyzing the maximum number of mitigation practices available. The paper concludes by identifying eight most impactful social sustainability practices that can help resolve the maximum number of implementation barriers and highlights avenues for further research in the field.